The Effectiveness of Occupational Therapy on Patients with Schizophrenia or Another Mental Illness: A Systematic Review - Yuli Anggraini; Ahmad Wahyudi; Dutya Intan Larasati; Ah Yusuf (Jurnal Ners, 2020)
Introduction: A growing body of literature has shed light on occupational therapy (OT) interventions and outcomes in relation to mental illness. The purpose of this article is to provide an overview of the OT interventions used with patients with schizophrenia or mental illness and their documented outcomes in relation to functional level, well-being and quality of life.Methods:  The databases searched were Scopus, Proquest, Sage, and Pubmed and the time of publication was in the last ten years. This was limited by the journal source type. The search terms, truncated when relevant, were "schizophrenia," "mental illness,"  “work training,” “occupational therapy” and “vocational therapy”.Results: Thirteen peer-reviewed intervention studies targeting adults with mental illness or schizophrenia were reviewed and analyzed. There are 6 categories related to the occupational interventions that emerged: skill training, cognitive-based occupational treatment, psychosocial-based occupational therapy, cognitive behavior therapy-based occupational therapy, creative occupational therapy, and peer group support-based occupational intervention.Conclusion: Most of the previous literature states that there were significant effects from the occupational therapies on the level of functioning, well-being or quality of life of the patients with schizophrenia or mental illness.